Analysis methods fixing racks for carrying heavy loads - Штефан, Тетяна Олександрівна (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2015)
Studied the deformation front, which weighs a heavy load in the event of a flat elastic deformation. The problem is solved in a static setting by trigonometric series. Two types of conditions at the lower boundary along which stand paired with a completely rigid half. A numerical study of the potential energy function of forming, which is used in the energy hypothesis of strength, and develop practical recommendations for fixing stand on the platform.